Atrial Fibrillation Screen, Management, and Guideline‐Recommended Therapy in the Rural Primary Care Setting: A Cross‐Sectional Study and Cost‐Effectiveness Analysis of eHealth Tools to Support All Stages of Screening - Orchard, Jessica (J Am Heart Assoc, 2020)
BACKGROUND: Internationally, most atrial fibrillation (AF) management guidelines recommend opportunistic screening for AF in people ≥65 years of age and oral anticoagulant treatment for those at high stroke risk (CHA₂DS₂‐VA≥2). However, gaps remain in screening and treatment. METHODS AND RESULTS: General practitioners/nurses at practices in rural Australia (n=8) screened eligible patients (≥65 years of age without AF) using a smartphone ECG during practice visits. eHealth tools included electronic prompts, guideline‐based electronic decision support, and regular data reports. Clinical audit tools extracted de‐identified data. Results were compared with an earlier study in metropolitan practices (n=8) and nonrandomized control practices (n=69). Cost‐effectiveness analysis compared population‐based screening with no screening and included screening, treatment, and hospitalization costs for stroke and serious bleeding events. Patients (n=3103, 34%) were screened (mean age, 75.1±6.8 years; 47% men) and 36 (1.2%) new AF cases were confirmed (mean age, 77.0 years; 64% men; mean CHA₂DS₂‐VA, 3.2). Oral anticoagulant treatment rates for patients with CHA₂DS₂‐VA≥2 were 82% (screen detected) versus 74% (preexisting AF)(P=NS), similar to metropolitan and nonrandomized control practices. The incremental cost‐effectiveness ratio for population‐based screening was AU$16 578 per quality‐adjusted life year gained and AU$84 383 per stroke prevented compared with no screening. National implementation would prevent 147 strokes per year. Increasing the proportion screened to 75% would prevent 177 additional strokes per year. CONCLUSIONS: An AF screening program in rural practices, supported by eHealth tools, screened 34% of eligible patients and was cost‐effective. Oral anticoagulant treatment rates were relatively high at baseline, trending upward during the study. Increasing the proportion screened would prevent many more strokes with minimal incremental cost‐effectiveness ratio change. eHealth tools, including data reports, may be a valuable addition to future programs. REGISTRATION: URL: https://www.anzctr.org.au. Unique identifier: ACTRN12618000004268.